The relationship between maternal personal hygiene and the incidence of diarrhea in toddlers at the cibeureum health center - Anastasia Y Triningtyas; Emma M Hidayat; Beryl E Widyaningrum (ACTA Medical Health Sciences, 2025)
Diarrhea is one of the leading causes of mortality in children under five years of age. Hygienic living behavior plays a crucial role in preventing the transmission of diarrhea. Maternal behavior is closely associated with the prevention and reduction of diarrhea in toddlers. This study aims to describe and determine the relationship between maternal knowledge, attitudes,and personal hygiene practices and the incidence of diarrhea among toddlers at the Cibeureum Public Health Center, South Cimahi, Indonesia. This study employed an analytical crosssectional design. Data were collected from 70 respondents using a consecutive sampling technique. Information was obtained through structured questionnaires. Data analysis was conducted using the chi-square test and Fisher’s exact test. The results showed that the majority of mothers demonstrated good levels of knowledge, positive attitudes, and personal hygiene practices. Accordingly, 81.4% of toddlers were reported to rarely experience diarrhea (p-value = 0.22). Statistical analysis indicated no significant relationship between maternal knowledge, attitudes, and personal hygiene practices and the incidence of diarrhea in toddlers. These findings suggest that multiple factors contribute to the occurrence of diarrhea in toddlers. Nevertheless, adequate knowledge, positive attitudes, and personal hygiene practices remain important preventive measures against diarrhea in this population.   DOI: 10.35990/amhs.v4n2.p94-102   REFERENCES Indonesian Pediatric Society (IDAI). Textbook of Gastroenterology–Hepatology. I. Jakarta: Pediatric Gastroenterology–Hepatology Working Group, IDAI; 2009. World Health Organization. The Treatment of Diarrhoea: A Manual for Physicians and Other Senior Health Workers. Geneva: WHO; 2005. World Health Organization. Diarrhoeal disease [Internet]. Tersedia pada:https://www.who.int/newsroom/fact-sheets/detail/diarrhoeal-disease Ministry of Health of the Republic of Indonesia. 2022 Performance Report: Directorate of Communicable Disease Prevention and Control. Jakarta: Ministry of Health of the Republic of Indonesia; 2023. Heryanto E, Sarwoko S, Meliyanti F. Risk factors of diarrhea in children under five at UPTD Sukaraya Health Center, OKU District, 2021. Indonesian Journal of Health Medicine. 2022;2:10–21. Sipayung RR, Sinurat LRE, Pardede JA. Improving maternal knowledge in the prevention and management of diarrhea in children under five at Bestari Health Center. Tour Abdimas Journal. 2023;2:1–7. Indrayani M. Correlation between maternal knowledge of personal hygiene and diarrhea incidence in children under five at Imelda Workers General Hospital, Medan, 2020. Journal of Health Medical Science. 2022;1:110–116. Aisyah IS. Analysis of the correlation between hygienic practices and diarrhea incidence: Case of Jagabaya Hamlet. Nusantara Journal of Health and Midwifery. 2024;5(039):6–9. Santri IN, Wardani Y. Environmental risk factors of diarrhea in children under five: A cross-sectional study in Indonesia. Public Health and Preventive Medicine Archive. 2023;11. Indonesian Pediatric Society (IDAI). Digestive problems in children: Causes and solutions [Internet]. Tersedia pada:https://www.idai.or.id/artikel/seputar-kesehatan-anak/masalah-saluran-cerna-anak-penyebab-dan-mengatasinya Lestari F, Azahra H, Neng A, Rizka A, Salma A. Factors associated with diarrhea in infants and toddlers at Diny Nahrudiani Midwifery Clinic, Karacak Village, Leuwiliang Subdistrict, Bogor Regency. Student Scientific Journal and Nursing Research. 2024;9. Amir ETP, Erlani, Ain K. Maternal personal hygiene and diarrhea incidence in children under five at Bajoe Health Center, Bone Regency. Jurnal Sulolipu: Academic and Community Communication Media. 2024;24:296–305. Ningsih SA, Putri DUP, Maritasari DY. Correlation between knowledge, personal hygiene, and diarrhea incidence in children under five. An Idea Health Journal. 2024;4:99–104. Simamora DN, Sihite H, Ogi MP. Correlation between maternal knowledge and attitudes on hygiene in preventing diarrhea in children under five at Pakkat Toruan Village, Doloksanggul Subdistrict, Humbang Hasundutan Regency, 2024. Jurnal Medika Kesehatan Baru Doloksanggul. 2024;2. Aghadiati F, Setyarsih L, Merlisia M, Simatupang YM. Correlation between personal hygiene and diarrhea incidence in children under five at Aur Duri Health Center, Jambi City. Bahana Journal of Public Health. 2023;6:10–14. Utama SYA, Inayati A, Sugiarto S. Association between family latrine conditions and clean water facilities with diarrhea in children under five in Arosbaya Health Center, Bangkalan. Dinamika Kesehatan: Midwifery and Nursing Journal. 2019;2:820–832. Maternal behavior in diarrhea prevention and its association with diarrhea incidence in toddlers aged 1–3 years at Mitra Medika Hospital. Community Health Journal. 2021;3:52–63. Widhiastiti IAMU, Nyoman S, Wayan S, Ayu MA. Correlation between maternal knowledge, attitude, and practices with diarrhea incidence in children under five at Bungaya Village, 2023. Journal of Environmental Health. 2023;2. Hermanita Y, Dian RA, Raja FL, Agnita U. Maternal attitudes in managing diarrhea in children under five. Journal of Public Health Sciences. Nurwahidah S, Prajayanti ED. Overview of maternal personal hygiene and its relation to diarrhea in children under five at Mliwis Village, Cepogo Subdistrict, Boyolali Regency. Jurnal Ilmu Kesehatan Mandira Cendikia. 2023;2:358–359. Cantika C, Mita, Yoga P, Ali M, Faisal KF. Maternal knowledge and attitudes regarding diarrhea in children under five in North Pontianak Subdistrict. BSI Nursing Journal. 2024;2. Noviyanti, F Siti. Correlation study of maternal personal hygiene and diarrhea in children under five in Surakarta City. Aisyiyah Surakarta Journal of Nursing.